The effect of the use of biostimulant on the yield and quality of lavandin and lavender - Teofil GAVRIĆ; Drena GADŽO; Renata ERHATIĆ; Katarina HAFNER-VUK (Notulae Botanicae Horti Agrobotanici Cluj-Napoca)
Lavandula species are one of the most popular aromatic plants in the world and have a high content of high-quality essential oil (EO). Although there are many species in this genus, only lavandin (Lavandula intermedia Emeric ex Loisel.) and lavender (L. angustifolia Mill.)  are highly valued worldwide. The quality and yield of lavandin and lavender depend on genetic factors, environmental conditions and cultivation methods. Therefore, the aim of this paper is to research the effects of the application of biostimulant on the inflorescence yield and the quality of lavandin and lavender. The treatments used in this research consisted of a combination of different species (lavandin and lavender) and biostimulant (applied and unapplied). The research results show that all the research traits significantly depended on the used species and the applied biostimulant. The inflorescence yield, the content of total flavonoids, and the content of EO were higher in the lavandin species (477.3 g plant-1, 17.21 mg CAE g-1, 8.57 mL 100 g-1, respectively) than in the lavender species (180.5 g plant-1, 13.41 mg CAE g-1, and 3.69 mL 100 g-1, respectively). EOs of lavandin and lavender were rich in linalool and linalyl acetate. The use of biostimulators had a positive effect on the inflorescence yield and the content of essential oil. Furthermore, the applied biostimulant increased the linalool content in the essential oil of both researched species, i.e. it positively affected its quality.